Systemic corticosteroids in coronavirus disease 2019 (COVID-19)-related smell dysfunction: an international view - Huart, Caroline; Philpott, Carl M; Altundag, Aytug; Fjaeldstad, Alexander W; Frasnelli, Johannes; Gane, Simon; Hsieh, Julien W; Holbrook, Eric H; Konstantinidis, Iordanis; Landis, Basile N; Macchi, Alberto; Mueller, Christian A; et al. (International forum of allergy & rhinology, 2021)
The frequent association between coronavirus disease 2019 (COVID-19) and olfactory dysfunction is creating an unprecedented demand for a treatment of the olfactory loss. Systemic corticosteroids have been considered as a therapeutic option. However, based on current literature, we call for caution using these treatments in early COVID-19-related olfactory dysfunction because: (1) evidence supporting their usefulness is weak; (2) the rate of spontaneous recovery of COVID-19-related olfactory dysfunction is high; and (3) corticosteroids have well-known potential adverse effects. We encourage randomized placebo-controlled trials investigating the efficacy of systemic steroids in this indication and strongly emphasize to initially consider smell training, which is supported by a robust evidence base and has no known side effects.
Keywords: Research Design; SARS-CoV-2; Needs Assessment; Olfactory Mucosa; Drug-Related Side Effects and Adverse Reactions; odhad potřeb; Global Health; celosvětové zdraví; lidé; čichová sliznice; Adrenal Cortex Hormones; COVID-19; hormony kůry nadledvin; smell; Olfaction Disorders; olfaction disorder; Medication Therapy Management; poruchy čichu; nežádoucí účinky léčiv; management farmakoterapie; spontánní remise; Remission, Spontaneous; výzkumný projekt; corticosteroids; Humans